Chronic Alcohol Exposure Induces Aberrant Mitochondrial Morphology and Inhibits Respiratory Capacity in the Medial Prefrontal Cortex of Mice - Shang, Pei; Lindberg, Daniel; Starski, Phillip; Peyton, Lee; Hong, Sa-Ik; Choi, Sun; Choi, Doo-Sup (Frontiers in Neuroscience, 2020)
Alcohol use disorder (AUD) is characterized as a chronic, relapsing disease with a pattern of excessive drinking despite negative consequences to an individual’s life. Severe chronic alcohol use impairs the function of the medial prefrontal cortex (mPFC), which contributes to alcohol-induced cognitive and executive dysfunction. The mPFC contains more mitochondria compared to other cortical areas, which suggests mitochondrial damage may occur in AUD and trigger subsequent behavior change. Here, we identified morphological and functional changes in mitochondria in the mPFC in C57BL6/J mice after 8 h of withdrawal from chronic intermittent alcohol (CIA) exposure. Three-dimensional serial block-face scanning electron microscopy (SBFSEM) reconstruction revealed that CIA exposure elongated mPFC mitochondria and formed mitochondria-on-a-string (MOAS). Furthermore, alcohol significantly affected mitochondrial bioenergetics, including oxidative phosphorylation and electron transport, with inhibited aerobic respiration in mPFC mitochondria after CIA exposure. We also found decreased expression of fusion (mitofusin 2, Mfn2) and increased fission (mitochondrial fission 1 protein, Fis1) proteins in the mPFC of alcohol-treated mice. In sum, our study suggests that CIA exposure impairs mitochondrial dynamics and function in the mPFC.